Pengaruh Flow Experience dan Parasocial Interaction pada Dorongan Pembelian Impulsif di Live Streaming Commerce - Agatha, Chindy; Emilio, Sean; Rahman, Fathony (Universitas Prasetiya Mulya, 2023)
Live streaming commerce is one of the results of technological development which is able to make human’s online shopping experience similar to offline shopping experience. Previous studiestend to discuss the factors that influence impulsive buying from one perspective, either flow experience or parasocial interaction. Therefore, this study aims to fill the gap by examining the influenceof flow experience and parasocial interaction towards the consumers’ urge to buy impulsively in live streaming commerce in Java Island through the Stimulus-Organism-Response (S-O-R) theory. The analysis of Structural Equation Modeling (SEM) was conducted on a sample of 409 respondents collected through convenience sampling technique who filled out an online questionnaire. This study resulted in three main findings: (a) platform design, time pressure, and personalized recommendation positively influence flow experience, (b) similarity, expertise, and likability positively influence parasocial interaction, and (c) parasocial interaction positively influence urge to buy impulsively in the context of live streaming commerce in Java Island.